Low density lipoprotein cholesterol decreases vascular cell adhesion molecule-1 in postmenopausal women - Pusparini, Pusparini; Wiradharma, Danny; Herwana, Elly (Universa Medicina, 2011)
In premenopausal women cardiovascular disease is rarely encountered, but after menopause the prevalence of cardiovascular disease increases drastically. There are several risk factors for cardiovascular disease, known as traditional risk factors, among others body fat concentration, age, duration of menopause, body mass index (BMI), and estradiol concentration. Cardiovascular disease is considered as an inflammatory disorder, in which adhesion molecules play an important role. Vascular cell adhesion molecule-1 (VCAM-1) is one of the adhesion molecules with an important role in the atherosclerotic process. The aim of this study was to determine the relationship of risk factors affecting the expression of VCAM-1 in postmenopausal women. This study was a cross-sectional study involving 182 postmenopausal women in the age range of 47- 60 years, who were residents of Mampang Prapatan subdistrict, South Jakarta. Venous blood samples were obtained for laboratory investigations, viz. fasting blood glucose, total cholesterol, high density lipoprotein (HDL) cholesterol, low density lipoprotein (LDL) cholesterol, triglycerides, creatinine, serum glutamic oxaloacetic transamirase (SGOT), serum glutamic pyruvic transmirasi (SGPT), bilirubin, total protein, albumin, estradiol and vascular cell adhesion molecule-1 (VCAM-1).A multiple regression analysis was performed on traditional risk factors and their relationship with VCAM-1 concentration. The results showed there were five traditional risk factors influencing VCAM-1 concentration, viz. duration of menopause, BMI, estradiol concentration, HDL cholesterol, and LDL cholesterol. Among these five factors, LDL cholesterol had the greatest influence on VCAM-1 expression (beta coefficient = -0.253 and p=0.001). In conclusion, LDL cholesterol concentration decreased VCAM-1 expression in postmenopausal women.